Éthique de l’intelligence artificielle et ubiquité sociale des technologies de l’information et de la communication : comment penser les enjeux éthiques de l’IA dans nos sociétés de l’information ? - Frédérick BRUNEAULT; Andréane SABOURIN LAFLAMME (Tic & Société)
Artificial intelligence (AI) plays an important role in current discussions on information and communication technologies (ICT) and new modes of algorithmic governance. It is an unavoidable dimension of how social mediations and modes of reproduction will evolve in our information societies. While several works in artificial intelligence ethics (AIE) address ethical issues specific to certain areas of expertise, these ethical reflections often remain confined to narrow areas of application, without considering the global ethical issues in which they fit. We therefore propose clarifying the main approaches to AIE, their philosophical assumptions and the specific characteristics of each, in order to identify the most promising approach to developing ethical reflections on the deployment of AI in our societies.